WiMAX: Network Entry Phase Optimization for Bandwidth Improvement Solution - Ghazali, Mohamad Firdaus; Shibghatullah, Abdul Samad; Sahib, Shahrin (2010)
Worldwide Interoperability for Microwave access (WiMAX) service providers is concerned about having enough Internet-backbone to support a potentially large number of users. Network entry process directly influences the initial delay that users are experiencing. Therefore, efficiently combine DCD interval, UCD interval and initial ranging interval in network entry process is predicted to influence the network performance, as presented in this paper.